1998
DOI: 10.1007/s001040050373
|View full text |Cite
|
Sign up to set email alerts
|

Postcholecystektomiebeschwerden ein Jahr nach laparoskopischer Cholecystektomie Ergebnisse einer prospektiven Untersuchung von 253 Patienten

Abstract: One year after laparoscopic cholecystectomy 93% of the patients have no or only minor abdominal symptoms. Neither the number and location of the laparotomies prior to cholecystectomy nor the loss of gallstones intraoperatively have an impact on the long-term result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 10 publications
1
6
0
1
Order By: Relevance
“…As patients had normal bile ducts in the preoperative MRCP, the stones must have been mobilized from the gallbladder during the operation. In the era before MRCP, when only IVC was used at our institute, residual stones occurred at a frequency of 1% [3,4]. Residual stones not only have the risk of recurrent gallstones-associated disease, as mentioned before, they can also make patients dissatisfied.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As patients had normal bile ducts in the preoperative MRCP, the stones must have been mobilized from the gallbladder during the operation. In the era before MRCP, when only IVC was used at our institute, residual stones occurred at a frequency of 1% [3,4]. Residual stones not only have the risk of recurrent gallstones-associated disease, as mentioned before, they can also make patients dissatisfied.…”
Section: Discussionmentioning
confidence: 93%
“…After detection, CBD stones were extracted by endoscopic retrograde cholangiopancreaticography (ERCP) prior to cholecystectomy. With the routine use of IVC, a rate of residual stones of 1% and a rate of bile duct injuries below 0.1% was observed [3,4]. Since 2005, we started to use magnetic resonance cholangiopancreaticography (MRCP) instead of IVC for preoperative investigation to reduce ionizing radiation, the risk of allergic reaction to contrast agent, and costs.…”
Section: Introductionmentioning
confidence: 97%
“…Peter et al in their study showed that 28% of patients have mild form, 5% moderate form and 2% of patients have severe form of PHS. According to this study, in 26% of patients the cause of the PHS is afunctional disorder of biliary secretion ( 5 ). This clinical entity is manifested with many non-specific subjective complaints: nausea, feeling of fullness, early satiation, epigastricpain, heartburn, vomiting, belching, bloating, flatulance, regurgitation.…”
Section: Discussionmentioning
confidence: 99%
“…One of the following criteria, therefore, had to be present: moderate or severe heartburn, moderate or severe acid regurgitation, esophagitis of at least grade II, the requirement of daily proton pump inhibitor (PPI) treatment or the need for reoperation because of GERD. Additionally, the symptomatic outcome was classified according to the modified Visick score (I = no symptoms; II = mild symptoms, no regular medication or physician’s help needed; III = significant symptoms, regular medication or physician’s help needed; IV = symptoms as bad as or worse than before surgery) [17]. The patients were asked whether they were able to belch and vomit, if they needed continuous PPI therapy, if endoscopy was necessary for any reason and if they had undergone a reoperation.…”
Section: Methodsmentioning
confidence: 99%